Subjective age and depressive symptoms among Chinese older adults: A moderated mediation model of perceived control and self-perceptions of aging. (January 2019) - Xiao, Luxia; Yang, Hang; Du, Weiping; Lei, Huijie; Wang, Zhi; Shao, Jingjin
Highlights: Younger subjective age is significantly associated with less depressive symptoms among Chinese older adults. Perceived control partially mediates the relationship between subjective age and depressive symptoms. The indirect effect of subjective age on depressive symptoms via perceived control is stronger for older adults with less favorable self-perceptions of aging. Abstract: Although subjective age has been shown to play an important role in older adults' experiences of depressive symptoms, the mediating and moderating mechanisms underlying this relationship have not been adequately examined. The present study aimed to investigate the mediating role perceived control plays between subjective age and depressive symptoms, as well as the moderating role self-perceptions of aging plays in this indirect relationship. To examine this, a cross-sectional study was conducted with 609 Chinese older adults, who completed measures of subjective age, perceived control, self-perceptions of aging, and depressive symptoms. The results indicated that: (1) possessing a younger subjective age is significantly associated with less depressive symptoms; (2) perceived control partially mediates the relationship between subjective age and depressive symptoms; and (3) the indirect effect of subjective age on depressive symptoms, through perceived control, is moderated by self-perceptions of aging, while the mediated path is stronger for older adults with less favorable self-perceptions of aging. The findings underscore the importance of identifying the mechanisms that moderate the mediated paths between subjective age and depressive symptoms.